Dual atmosphere study of the K41X stainless steel for interconnect application in high temperature water vapour electrolysis. (27th April 2015) - Ardigo, M.R.; Popa, I.; Combemale, L.; Chevalier, S.; Herbst, F.; Girardon, P.
Abstract: High temperature water vapour electrolysis (HTE) is one of the most efficient technologies for mass hydrogen production. A major technical difficulty related to high temperature water vapour electrolysis is the development of interconnects working efficiently for a long period. Working temperature of 800 °C enables the use of metallic materials as interconnects. High temperature corrosion behaviour and electrical conductivity of a commercial stainless steel, K41X (AISI 441), were tested in HTE dual atmosphere (95%O2 -5%H2 0/10%H2 -90%H2 O) at 800 °C. The alloy exhibits a very good oxidation resistance compared to single atmosphere tests. However, a supplied electrical current significantly changes the nature of the oxides that form during the test. A very good Area Specific Resistance (ASR) parameter was measured in dual atmosphere, much lower than the values obtained in single atmosphere tests. Highlights: A stainless steel tested as interconnect material for water steam electrolysis. Corrosion and conductivity tests in dual atmosphere (O2 -H2 O/H2 -H2 O) at 800 °C. The role of the dual atmosphere on the corrosion behaviour is discussed. The influence of the electrical current on the corrosion behaviour discussed. A very good ASR parameter obtained in dual atmosphere.